Vibrations and Waves in Physics - Iain G. Main (New York Cambridge University Press, 1994)
School of Mathematics and Natural Science
MIR No: 178
Order Date: 2024-09-09
Order No: CU/OPEX/LIBRARY/33/2024-25
Received Date: 2024-01-10
Keywords: Physics, Vibrations, Waves